An Extended Web Displaying System based on Multiple Tablet Devices - Shota Imai; Shun Shiramatsu; Tadachika Ozono; Toramatsu Shintani (International Journal of Networked and Distributed Computing (IJNDC), 2016)
We propose an extended Web displaying system based on multiple tablet devices to help users to conduct collaborative works anywhere without a large display. Users can use multiple tablet devices as a pseudo mobile large display on demand by using our system. For example, users can make discussions by using Web applications anywhere. We present management methods of the arranged displays and two types of synchronous messages. One uses positional information and the other uses operational information for Web page synchronization. We show two applications based on the extended Web displaying system, a piano score system and a map viewer system.